Efektivitas latihan ball mastery terhadap keterampilan dribbling pada pemain deny soccer academy U15 - Danuarta, Rafli Jaya; Apriliyanto, Rizki; Sulaiman, Ahmad (Physical Education Departement of University PGRI Jombang, 2025)
Research Problems: This study was motivated by the fact that the dribbling skills of Deny Soccer Academy U15 players still vary and most have not yet achieved stable performance, partly due to the tendency of players to spend more time using social media, which has resulted in low frequency of independent training and limited studies on the U15 age group. This study aims to analyse the effectiveness of ball mastery training in improving dribbling skills among players at Deny Soccer Academy U15. Methods: This study employed an experimental design with a one-group pretest–posttest model. A total of 20 U15 players were selected through purposive sampling based on the criteria of training activity and physical readiness. The ball mastery training programme was conducted over four weeks with a total of 16 training sessions, covering the sole tap, inside to inside, outside cut, inside outside, and pull push techniques. Dribbling ability was measured using the Bobby Charlton Slalom Dribbling Test before and after the treatment. Statistical analysis used descriptive tests, Shapiro Wilk normality tests, and paired sample t tests with a significance level of 0.05. Results: The results of the study showed a significant improvement in dribbling ability after participating in the ball mastery training programme. The average dribbling time decreased from 18.40 seconds in the pretest to 16.14 seconds in the posttest. The paired sample t-test showed a Sig. (2-tailed) value < 0.001, indicating a significant difference between the scores before and after the treatment. Conclusion: Ball mastery training has proven effective in improving the dribbling skills of Deny Soccer Academy U15 players. The training programme, which is structured, repetitive, and combined with static and dynamic warm-ups, improves ball control, speed of movement, and player stability when dribbling. This training can be an important part of warm-up sessions and technical training in youth football coaching. Keywords: Ball Mastery, Dribbling, Training, Football